DETERMINATION OF ROUTES AND MINIMIZATION OF CERAMIC DISTRIBUTION DISTANCE USING MATRIX SAVINGS METHOD (CASE STUDY: PT. LUCRO INDO JAYA) - Ismi Ana Sulasiyah; Dani Abdul Malik; Qurrotul Aini (Universitas Islam Indragiri, 2020)
ABSTRACTDistribution is part of logistics, with a fundamental function for the company. Distribution made from a source to various destinations makes this activity quite complex because the distribution channels that are adrift with a long-distance make the number of costs incurred for shipping. This study aims to minimize the delivery distance traveled in the distribution of ceramics to more than one retail by using the saving matrix method. The saving matrix method can schedule vehicles to distribute products from the central warehouse to several shipping routes. This research was conducted using data in the form of ceramic supply at the company, retail demand data, distance data, and shipping cost of ceramics in January-December 2018 with a total of 10 (ten) customer destinations located in Tangerang-Jakarta. The saving matrix method is optimized by using the method of Farthest Insert, Nearest insert and Nearest Neighbor in determining vehicle scheduling by sorting shipments that are considered more optimal. The results of this study are obtained savings of 14.5% with a total distance that was previously 302.9 km to 258.9 km and savings in shipping costs by 15% which previously was Rp 1,756,150,000 to Rp 1,501,047,326. The use of the saving matrix method is able to improve the order of shipping routes of the company's distribution so that it reduces shipping mileage and reduces the company's operating costs in terms of product distribution.Keywords: distribution, distance minimization, routing, saving matrixABSTRAKDistribusi merupakan bagian dari logistik, dengan fungsi fundamental bagi perusahaan. Pendistribusian yang dilakukan dari suatu sumber keberbagai tempat tujuan menjadikan kegiatan ini cukup komplek, dikarenakan jalur distribusi yang terpaut dengan jarak yang panjang menjadikan besarnya biaya yang dikeluarkan untuk pengiriman. Penelitian ini bertujuan meminimumkan jarak pengiriman yang ditempuh dalam distribusi keramik ke lebih dari satu retail dengan menggunakan metode saving matrix. Metode saving matrix dapat menjadwalkan kendaraan untuk melakukan pendistribusikan produk dari gudang central ke beberapa rute pengiriman. Penelitian ini dilakukan dengan menggunakan data berupa persediaan (supply) keramik pada perusahaan, data permintaan (demand) kebutuhan retail, data jarak dan biaya pengiriman keramik pada bulan Januari-Desember 2018 dengan total 10 (sepuluh) tujuan pelanggan yang berlokasi di Tangerang-Jakarta. Metode saving matrix dioptimalkan dengan penggunaan metode Farthest Insert, Nearest insert dan Nearest Neighbor dalam menentukan penjadwalan kendaraan dengan mengurutkan pengiriman yang dinilai lebih optimal. Hasil dari penelitian ini adalah diperolehnya penghematan sebesar 14,5% dengan total jarak yang sebelumnya 302,9 km menjadi 258,9 km dan penghematan biaya pengiriman sebesar 15% yang sebelumnya sebesar Rp 1.756.150.000 menjadi Rp 1.501.047.326. Penggunaan metode saving matrix mampu memperbaiki urutan pengiriman rute distribusi perusahaan sehingga mengurangi jarak tempuh pengiriman dan mengurangi biaya operasional perusahaan dalam hal distribusi produk.Kata Kunci: distribusi, minimasi jarak, routing, saving matrix